PreImplantation Factor (PIF*) Regulates Stress-Induced Adrenal Steroidogenesis and Anti-Inflammatory Cytokines: Potential Application for Bioartificial Adrenal Transplant - Balyura, Mariya; Gelfgat, Evgeny; Ullmann, Enrico; Ludwig, Barbara; Barnea, Eytan R.; Bornstein, Stefan R. (Hormone and Metabolic Research, 2018)
The main treatment algorithm for adrenal insufficiency is hormonal replacement, however, inadequate hormone substitution often leads to severe side effects. Adrenal cell transplantation could be a more effective alternative but would require life-long immune suppressive therapy. PreImplantation Factor (PIF) is an endogenous peptide secreted by viable human embryos that leads to maternal tolerance without immunosuppression. PIF could be effective for xenogeneic cell transplantation such as of bovine adrenocortical cells (BAC), which are used for bioartificial adrenal gland development that may more effectively restore complex adrenal functions. We report here that PIF exerts a dual regulatory effect on BAC by targeting mostly hyper-activated cells to specifically reduce adrenocorticotropic hormone (ACTH)-stimulated cortisol secretion. Reverse transcription real time PCR analysis revealed that PIF modulates the expression of two genes in the cortisol synthesis pathway, Steroidogenic Factor 1 (SF1), an activator of steroidogenesis, and the downstream steroidogenic enzyme Cytochrome P450 17A1 (CYP17A1). PIF increased basal expression of SF1 and CYP17A1 regardless of the activation level of the adrenocortical cells. In contrast, following ACTH stimulation, PIF reduced SF1 expression and induced expression of the immune suppressing anti-inflammatory cytokine IL10 only in the hyper-activated cells, suggesting both a protective and immune tolerant function. In conclusion, PIF regulates stress-induced adrenal steroidogenesis and immune tolerance in BAC, supporting a potential clinical application to reduce rejection by the host’s immune response following xenotransplantation.
Keywords: adrenocortical cells; immune tolerance; immune regulation